2016
DOI: 10.1073/pnas.1601611113
|View full text |Cite
|
Sign up to set email alerts
|

Armed-conflict risks enhanced by climate-related disasters in ethnically fractionalized countries

Abstract: Social and political tensions keep on fueling armed conflicts around the world. Although each conflict is the result of an individual context-specific mixture of interconnected factors, ethnicity appears to play a prominent and almost ubiquitous role in many of them. This overall state of affairs is likely to be exacerbated by anthropogenic climate change and in particular climate-related natural disasters. Ethnic divides might serve as predetermined conflict lines in case of rapidly emerging societal tensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
204
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(215 citation statements)
references
References 63 publications
9
204
0
2
Order By: Relevance
“…This perspective fits within a growing body of literature that investigates links between climate-related disasters and conflict in different parts of the world (Bernauer et al 2012, Theisen et al 2013, Schleussner et al 2016. In this paper, we highlight the importance of looking at the actual vegetation changes taking place on the ground in connection to the reduction in precipitation during the drought years.…”
Section: Resultsmentioning
confidence: 79%
“…This perspective fits within a growing body of literature that investigates links between climate-related disasters and conflict in different parts of the world (Bernauer et al 2012, Theisen et al 2013, Schleussner et al 2016. In this paper, we highlight the importance of looking at the actual vegetation changes taking place on the ground in connection to the reduction in precipitation during the drought years.…”
Section: Resultsmentioning
confidence: 79%
“…S10 for examples of climate networks of several El Niño and La Niña events. Evidently, these enhanced and localized El Niño effects are associated with serious consequences in many aspects of human life (59)(60)(61)(62). In Fig.…”
mentioning
confidence: 98%
“…One out of the three studies found a direct effect on civil conflict onset [46,82,83], and the three studies that analyze incidence, duration, and battles also find these to be more likely in the wake of a disaster [46,57,84] (not in Table 1). Overall, in the period under review, too few studies were conducted to draw firm conclusions, but as for temperature, results opposite of the scarcity scenario seem unlikely.…”
Section: Empirical Studies 2014-2017mentioning
confidence: 99%